2021
DOI: 10.1101/2021.11.12.21266226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Remote Digital Memory Composite to Detect Cognitive Impairment in Memory Clinic Samples in Unsupervised Settings using Mobile Devices

Abstract: INTRODUCTIONMobile app-based unsupervised monitoring of cognition holds the promise to facilitate case-finding in clinical care and the individual detection of cognitive impairment in clinical and research settings. In the context of Alzheimer’s disease, this is particularly relevant for patients who seek medical advice due to memory complaints.OBJECTIVEWe developed a Remote Digital Memory Composite score from an unsupervised remote and mobile cognitive assessment battery focused on episodic memory and long-te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 45 publications
(53 reference statements)
3
16
0
Order By: Relevance
“…For example, a composite measure of the Boston Remote Assessment for Neurocognitive Health (BRANCH) ( 19 ) was strongly correlated with the PACC5 ( r = 0.62) in cognitively normal participants. Another recent study ( 34 ) used a composite of similar but not identical tasks as used in this study and demonstrated a strong correlation to PACC ( r = 0.51) in cognitively normal individuals without cognitive complaints. A study using the Ambulatory Research in Cognition app ( 15 ) in primarily cognitively normal participants (again using a composite of cognitive measures) reported a strong correlation with a global composite similar to the PACC ( r = −0.53).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…For example, a composite measure of the Boston Remote Assessment for Neurocognitive Health (BRANCH) ( 19 ) was strongly correlated with the PACC5 ( r = 0.62) in cognitively normal participants. Another recent study ( 34 ) used a composite of similar but not identical tasks as used in this study and demonstrated a strong correlation to PACC ( r = 0.51) in cognitively normal individuals without cognitive complaints. A study using the Ambulatory Research in Cognition app ( 15 ) in primarily cognitively normal participants (again using a composite of cognitive measures) reported a strong correlation with a global composite similar to the PACC ( r = −0.53).…”
Section: Discussionmentioning
confidence: 69%
“…In the course of the follow-up in-clinic examination, 692 of 879 participants have thus far been invited to participate in a two-year study using the neotiv-App ( 12 , 34 ). Of these, 172 participants have signed the informed consent and initiated the mobile app-based cognitive testing to date.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, while age-related memory impairment as well as differences between subjectively stable and declining groups are as expected, future studies combining in-clinic and unsupervised remote assessments need to define convergent and discriminant validity in detail in comparison with established neuropsychological assessment batteries. Recently, we could show that the same memory tests used here, combined to a composite score, are suitable to detect mild cognitive impairment in a memory-clinic population, and show high construct validity with an in-clinic neuropsychological assessment ( 37 ).…”
Section: Discussionmentioning
confidence: 94%
“…Taken together, while age-related memory impairment as well as differences between subjectively stable and declining groups are as expected, future studies combining in-clinic and unsupervised remote assessments need to define convergent and discriminant validity in detail in comparison with established neuropsychological assessment batteries. Recently, we could show that the same memory tests used here, combined to a composite score, are suitable to detect mild cognitive impairment in a memory-clinic population, and show high construct validity with an in-clinic neuropsychological assessment (Berron et al, 2021).…”
Section: Worse Task Performance With Higher Age and Subjective Memory...mentioning
confidence: 89%